2022
DOI: 10.1039/d1qo01358k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nitrogen-tethered 1,6-enynes through CuI/TFA catalysis

Abstract: A novel method for the concise and effective construction of the nitrogen-tethered 1,6-enynes in moderate to good yields was developed. This transformation involves a TFA-promoted Pictet-Spengler reaction/iminium formation, copper-catalyzed alkyne-iminium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, Feng and coworkers reported a CuI/TFA catalysis system to catalyze the domino Pictet-Spengler reaction/ A 3 -type coupling/1,5-hydride transfer/alkynylation in 2022 (►Scheme 26). 92 The mechanism studies showed that TFA promoted the Pictet-Spengler reaction of 2-arylethan-1-amines 106 and formaldehyde to form tetrahydroisoquinolines, followed by a reaction with another molecule of formaldehyde to give iminium ion, then Cu-catalyzed intermolecular hydride transfer and alkynylation with two molecules of To make the three-component Pictet-Spengler reaction greener, in recent years, enzyme catalysis, Brønsted acid, and Lewis acid-free strategies have received considerable attention. For example, α-amylase activation catalysis is an alternative protocol for the generation of highly substituted indoquinolines 113, which was uncovered by He and coworkers in 2019 (►Scheme 27).…”
Section: Three-component Pictet-spengler Cyclization-based Domino Rea...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Feng and coworkers reported a CuI/TFA catalysis system to catalyze the domino Pictet-Spengler reaction/ A 3 -type coupling/1,5-hydride transfer/alkynylation in 2022 (►Scheme 26). 92 The mechanism studies showed that TFA promoted the Pictet-Spengler reaction of 2-arylethan-1-amines 106 and formaldehyde to form tetrahydroisoquinolines, followed by a reaction with another molecule of formaldehyde to give iminium ion, then Cu-catalyzed intermolecular hydride transfer and alkynylation with two molecules of To make the three-component Pictet-Spengler reaction greener, in recent years, enzyme catalysis, Brønsted acid, and Lewis acid-free strategies have received considerable attention. For example, α-amylase activation catalysis is an alternative protocol for the generation of highly substituted indoquinolines 113, which was uncovered by He and coworkers in 2019 (►Scheme 27).…”
Section: Three-component Pictet-spengler Cyclization-based Domino Rea...mentioning
confidence: 99%
“…In addition, Feng and coworkers reported a CuI/TFA catalysis system to catalyze the domino Pictet–Spengler reaction/A 3 -type coupling/1,5-hydride transfer/alkynylation in 2022 ( Scheme 26 ). 92 The mechanism studies showed that TFA promoted the Pictet–Spengler reaction of 2-arylethan-1-amines 106 and formaldehyde to form tetrahydroisoquinolines, followed by a reaction with another molecule of formaldehyde to give iminium ion, then Cu-catalyzed intermolecular hydride transfer and alkynylation with two molecules of terminal alkyne 108 to deliver nitrogen-tethered 1,6-enynes 109 with high selectivity.…”
Section: Three-component Pictet–spengler Cyclization-based Domino Rea...mentioning
confidence: 99%
“…However, the direct catalytic generation of alkynylides from terminal alkynes is possible due to their inherent acidity (RCCH, p K a = 25). Indeed, metal-catalyzed additions of terminal alkynes to aliphatic aldehydes and ketones, 12 a nitrones, 12 b and imines 13,14 have been documented (Scheme 2b).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously communicated the preliminary results of this investigation. 19 In view of the importance of propargylamines as versatile intermediates in organic synthesis, 13,15,20 the scope of this method was further extended. Moreover, the more challenging direct catalytic reductive alkylation of amides was envisioned.…”
Section: Introductionmentioning
confidence: 99%